Firefly optimization-based segmentation technique to analyse medical images of breast cancer. Issue 7 (3rd July 2021) - Kaushal, C.; Kaushal, Kirti; Singla, A.
Abstract : Nature-inspired algorithms emulate the mathematical and innovative techniques for non-linear and real-life problems worldwide. Imaging technology is emerging out as one of the most prominent and widely used domain in medical field such as cancerous cell nuclei detection, blood vessel segmentation, study of organs or structure of tissues and many more. Nature-inspired algorithms emulate the mathematical and innovative techniques for non-linear and real-life problems and can be applied to segment or analyse the images. An efficient image segmentation technique may help the subject experts such as radiologist and pathologist for early and effective examination or diagnosis of disease. The authors proposed a firefly-based segmentation technique that can be employed to segment the breast cancer image regardless the type or modality of the image. The effectiveness of the proposed technique is validated by comparing the procured results with the existing state-of-art techniques.